2020
DOI: 10.1007/s10853-020-05115-2
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porous poly(l-lactic acid)/SiO2 nanoparticles fibrous membranes for oil/water separation

Abstract: A two-step strategy has been developed to introduce silica nanoparticles into highly porous poly(l-lactic acid) (PLLA) nanofibers. Silica nanoparticles (SiNPs) were firstly synthesized and then modified to be hydrophobic. After PLLA/SiNPs composite fibrous membranes were electrospun and collected, they were re-crystallized by acetone at room temperature for a few minutes. With the re-arrangement of PLLA chains, the nano-/micro-electrospun fibres were transformed from non-porous ones to be porous ones with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…It is widely recognized that PLLA is a hydrophobic material. Therefore, the water contact angle of PLLA samples in this research was 144.9 ± 2.3° as expected . The deposition of copper particles onto the fibrous membrane made the surface rougher with higher contact angle .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…It is widely recognized that PLLA is a hydrophobic material. Therefore, the water contact angle of PLLA samples in this research was 144.9 ± 2.3° as expected . The deposition of copper particles onto the fibrous membrane made the surface rougher with higher contact angle .…”
Section: Resultssupporting
confidence: 79%
“…Therefore, the water contact angle of PLLA samples in this research was 144.9 ± 2.3°as expected. 62 The deposition of copper particles onto the fibrous membrane made the surface rougher with higher contact angle. 63 Furthermore, copper particles could act as a nonwetting material, thereby increasing the hydrophobicity of the surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, porous PLA fibers can also be prepared by some advanced electrospinning techniques such as blending spinning or coaxial spinning [ 39 , 40 ]. Moreover, several existing studies indicated the acetone post-treatment seemed to be an effective strategy for the increase of pore number and specific surface area of PLA fibers [ 17 , 41 ]. However, how to generate porous PLA nanofibers with decreased and uniform diameter and improved pore size and porosity still remains a huge challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, BET results for other samples are not provided. Due to the complex pore structure of the hierarchical porous PLLA@TiO 2 membrane surface and the wide distribution of pores, with pore sizes ranging from a few nanometers to several hundred nanometers, the BET measurements do not provide accurate information on the pores of the membranes. , As the TiO 2 NPs contents increase, the porous structures of the PLLA fiber surface decrease and are replaced by numerous TiO 2 NPs. This result suggests that the addition of large amounts of TiO 2 NPs may prevent the solvent-induced crystallization of PLLA fibers into surface porous structures by the acetone solution.…”
Section: Results and Discussionmentioning
confidence: 99%